2008
DOI: 10.1097/cji.0b013e3181880f1e
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Dendritic Cells and Chemoradiation for the Treatment of Murine Squamous Cell Carcinoma

Abstract: Dendritic cells are potent antigen presenting cells that have been shown to have significant antitumor effects in vitro and in vivo. However, the therapeutic efficacy of dendritic cells as an immunotherapeutic treatment has been limited by both immunologic tolerance and active immunosuppression in the tumor microenvironment. To address this problem, we examined the ability of concurrent systemic chemotherapy and local, fractionated radiation to augment intratumoral dendritic cell injections in a mouse model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
0
14
0
1
Order By: Relevance
“…SCC7 is a spontaneously arising squamous cell cancer syngeneic to C3H mice also described in our previous report (29). …”
Section: Methodsmentioning
confidence: 73%
“…SCC7 is a spontaneously arising squamous cell cancer syngeneic to C3H mice also described in our previous report (29). …”
Section: Methodsmentioning
confidence: 73%
“…Only after treatment the development of tumor-specific immune responses was observed in 52.9% of patients. This trial was not designed to test what the individual components of therapy would induce immune responses in vivo in human; however murine data from our and other groups 7–12 suggest that individually either DC or radiation is not sufficient to generate curative tumor-specific immune response or infiltration of tumor site with T-lymphocytes. We believe that these results are promising enough to warrant further trials.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of pre-clinical studies we and others have demonstrated that local tumor irradiation in combination with intratumoral DC administration but not irradiation alone resulted in potent antitumor immune responses that translated into an antitumor effect 7–12 . These preclinical studies provided a compelling rationale for testing this approach in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies show that local tumor irradiation in combination with immunotherapy can be used as an effective therapeutic strategy to improve treatment outcome [54]. It was reported that an intratumor injection of DC vaccination could synergize with radiation and then increase tumor-specific Tcell priming [55], and also extend survival in murine models [56]. Local irradiation combining with a cancer vaccine expressing human papilloma virus E6/E7 oncoproteins, made an 85-fold increase in the ratio of antitumoral CD8 + T cells to immune MDSC at the tumor site in mice [50].…”
Section: Local Tumor Irradiationmentioning
confidence: 99%